Influence of seasonal variation and anthropogenic activity on phosphorus cycling and retention in mangrove sediments: A case study in China. (5th March 2018) - Jiang, Shan; Lu, Haoliang; Liu, Jingchun; Lin, Yushan; Dai, Minyue; Yan, Chongling
Abstract: Mangroves are known for sequestering and storing large quantities of phosphorus (P) within their sediments. In the present study, the sediment P cycle (including phosphatase activity intensity, total sedimentary P, P fractions distinguished by a sequential extraction method, as well as diffusion-adsorption processes) in a mangrove swamp in a subtropical estuary in China was studied. In the spring, the acid phosphatase activity varied between 1.3 and 1.9 units in the four sites in the estuary. The activity of alkaline phosphatase varied from 0.8 to 1.4 units. The total sedimentary P ranged from 821 to 1689 mg kg −1 with a dominance of redox-sensitive (Fe/Al bound) P. In the autumn, activities of both phosphatases and the total sediment P amount increased, probably due to enhanced inputs of organic matter and Fe oxides. In addition to seasonal variation, P in the mangrove sediment was influenced by anthropogenic activities. In particular, redox-sensitive P decreased significantly while phosphatase activity increased in the site that was flushed with aquaculture pond effluents. In contrast, sediment P enrichment was observed in the site that received domestic sewage. Both sources of anthropogenic P increased the eutrophication risk of the mangrove sediment because of a decrease in the amount of P adsorption and an enhancement of P release via diffusion. Diesel contamination due to the presence of a dock depressed phosphatase activity in the surficial sediment. The overlap between seasonal rhythm and human influences may introduce significant variations in P cycling, which warrants further attention from coastal management. Graphical abstract: Image 1 Highlights: P storage and cycling in mangrove sediments were examined. Total sedimentary P and phosphatase activity showed seasonal variations. Aquaculture pond effluents decreased sedimentary P storage via reducing iron content. Domestic sewage enriched with reactive P increased sedimentary P concentration. The presence of a dock and related deforestation depressed phosphatase activity.